Free bus passes, use of public transport and obesity among older people in England. Issue 2 (12th September 2011) - Webb, Elizabeth; Netuveli, Gopalakrishnan; Millett, Christopher
Abstract : Background: All residents of England aged 60 years and older became entitled to free travel on local buses on 1 April 2006. This study examines the impact of this policy on public transport use, a mode of active transport and levels of obesity. Methods: Logistic regression analyses using three waves of data (2004, 2006 and 2008) from the English Longitudinal Study of Ageing. Our main outcome measures were changes in self-reported public transport use, body mass index, waist circumference and obesity. Results: Eligibility for free bus travel was associated with increased use (adjusted odds ratio (AOR) 1.51, 95% CI 1.14 to 2.00) of public transport among older people. Older people who used public transport had reduced odds of being obese in 2008 compared with those who did not (AOR 0.75, 95% CI 0.65 to 0.86), as did those who were eligible for free local bus travel (AOR 0.75, 95% CI 0.59 to 0.97). Older people who used public transport had reduced odds of becoming obese between 2004 and 2008 (AOR 0.79, 95% CI 0.63 to 0.98). Conclusion: The introduction of free bus travel for older residents of England appears to have increased public transport use and may have conferred a protective effect against obesity.